2019
DOI: 10.31744/einstein_journal/2019ao4526
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial comparing radiofrequency ablation and complete saphenous vein stripping in patients with mild to moderate chronic venous disease with a 3-year follow-up

Abstract: Objective: To compare the use of the radiofrequency thermoablation of the saphenous vein with the ligation technique, and complete removal of the saphenous vein, from the saphenofemoral junction to the ankle. Methods: A total of 49 patients with chronic venous disease in the Comprehensive Classification System for Chronic Venous Disorders (CEAP) classes 2 to 4 for clinical signs, etiology, anatomic distribution and pathophysiology, were assessed at baseline, after 4 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…There was no statistically signicant difference in gender distribution among the study groups. [5] Similarly in a study done by Igor Rafeal Sincos et al showed that the mean age among patients of stripping group was 49.3 ± 11.7 years and in patients of RFA group was 44.1 ± 11.7 years which was not signicant (P value 0.128) among the study groups. Also in the study it was showed there was no statistical signicant difference in gender Similarly in a study done by Eleftherios S Xenos, Gabriel Bietz, David [6] J Minion et al showed the mean age of the patients of stripping group was 48.4 ± 5.44 years and in patients of RFA group was 47 ± 7.48 years which was not statistically signicant (P value 0.69).…”
Section: Discussionmentioning
confidence: 81%
“…There was no statistically signicant difference in gender distribution among the study groups. [5] Similarly in a study done by Igor Rafeal Sincos et al showed that the mean age among patients of stripping group was 49.3 ± 11.7 years and in patients of RFA group was 44.1 ± 11.7 years which was not signicant (P value 0.128) among the study groups. Also in the study it was showed there was no statistical signicant difference in gender Similarly in a study done by Eleftherios S Xenos, Gabriel Bietz, David [6] J Minion et al showed the mean age of the patients of stripping group was 48.4 ± 5.44 years and in patients of RFA group was 47 ± 7.48 years which was not statistically signicant (P value 0.69).…”
Section: Discussionmentioning
confidence: 81%
“… 16 - 19 Despite all of these benefits, scientific evidence from well-designed studies and long-term studies proving the superiority of endovenous techniques is still lacking. When compared, both offer similar improvement in quality of life 20 , 21 and both are considered safe and effective. 19 Long-term recurrence is still questioned, although the results for the two techniques after 3-5 years are similar, particularly when vascular US with Doppler is employed intraoperatively during conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Long-term recurrence is still questioned, although the results for the two techniques after 3-5 years are similar, particularly when vascular US with Doppler is employed intraoperatively during conventional surgery. 20 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a subgroup meta-analysis by Bos et al in 2009 showed no significant differences in effectiveness between RFA and stripping [178]. Similarly, several other clinical trials evaluating RFA versus stripping surgery demonstrated improvement in clinical symptom indices without significant differences between treatment arms [188][189][190][191][192]. As with EVLA, RFA was found to result in lower immediate postoperative pain, lower complication rate, and decreased hospital length of stay [193].…”
Section: Radio-frequency Ablation (Rfa)mentioning
confidence: 99%